Malaysia and China students’ feedback on the implementation of critical thinking pedagogy: a case study - Azid, Nurulwahida; Hashim, Ridzuan; Tee, Tze Kiong; Yee, Mei Heong (SERSC, 2020)
Having a knowledgeable and highly skilled human capital is an important factor for Malaysia to transform its economy towards achieving a developed nation and high-income status by the year 2020. Hence, the Malaysian government strives to improve the enrolment of local and international post-graduate students by providing an effective learning process to ensure their quality. This research aimed at describing the impact of critical thinking pedagogy using case-based learning in curriculum studies course among postgraduate students. It was a case study with qualitative approach. Interview technique was used in this study whereby five students who enrolled in curriculum studies course were selected as the respondents. The study sample underwent learning through critical thinking pedagogy using SCSCBL interactive application. Overall, the findings showed that the teaching approach of using the case-based learning can promote critical thinking skills among pre-service and in-service teachers. This study has provided positive implications on the postgraduates’ soft skill development as preparation for their future career.